El centro histórico de Morelia: gestión social y revaloración del patrimonio - Cabrales Barajas, Luis Felipe (Anales de Geografía de la Universidad Complutense, 2002)
The historic center of Morelia is one of the most stately and best conserved in México, so much so that in 1991 it was declared a Patrimony of Humanity site by UNESCO. Notwithstanding such a mark of distinction, the last 25 years have seen the center invaded by a proliferation of street vendors, a problem that until recently seemed insoluable. It generated not only social and environmental problems but also limited the enjoyment to the public spaces by residents and tourists alike. Thanks to consensual political action and multiple negotiations, the more than 1.500 vendors were removed and relocated in more appropriate locations, leaving the city center to better exhibit its pleasant environment and distinguished architectural past. The paper documents the methods uses in relocation process, especially the role played by the Patronato Pro-Rescate del Centro Histórico to achieve this important objective which, for Mexico, appears most encouraging and has generated a climate of optimism.
Keywords: Historic center; Informal commerce; Morelia; México